Eksistensialisme Himura Kenshin dalam Serial Rurouni Kenshin - Barimbing, Theresa Laurenzi; Sutanto, Marisa Rianti; Lewerissa, Ethel Deborah (Vocational College of Diponegoro University, 2024)
This article aims to analyze the process of Himura Kenshin as the main character to achieve his existence by referring to Heidegger's theory of existentialism in Keishi Otomo’s Rurouni Kenshin film series. Rurouni Kenshin film series tells the life journey of Hitokiri Battosai, a samurai who worked as a government assassin, but decided to become a wanderer and stop killing in the Meiji era. The method used in this research is qualitative content analysis method. According to Heidegger, human (dasein) achieves their existence after going through three stages, namely moodness, fallenness, and sorge. The moodness stage guides Kenshin in making decisions to achieve his desired state in the world. The stage of fallenness allows Kenshin to understand himself and realize his existence. The stage of sorge, which is defined as 'care', involves anxiety about future possibilities as well as the urge to care for the world. Kenshin, as a human being, desires to exist and find his identity to harmonize with the world around him. Kenshin feels responsible for his past sins and decides to atone for them by helping others. After passing through all these stages, Kenshin achieves self-existence by being recognized as Himura Kenshin.